ANALISIS FAKTOR KULTUR PERUSAHAAN PADA TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP ASPEK LINGKUNGAN (Studi pada Perusahaan Nasional dan Multinasional di Indonesia) - Retno Widowati pA (FE UMY, 2015)
Corpardte social responstbility trt lcrnt of management oriertletton Utilitns No. 8/Tahun Ke-6/1998 27 torically from profit ndxi xitcd to tru,stee.ship to quaritt, ol rifc nnnagemiinT. rlte Jirst approach focused on sharelxtldcr interest, Ltnd the secontl v,as concerned to orgoniza_ lional slakeholder group,\ i e enlplolaes,ctrslomers, sttpltlicr, and yenclors,antl thc lasl QTte would brouden ir conccrns to external societal inreresrs, itrcluLling issues of environment The ctccelerated growth fu the nuntber ofmultinational crtrprtrolions (MNC;) and their v,orldwide scope, \,rith concentration of economic and political power tlrew atte ntion to c orporat e s oc ial r e s p on.: ib il ity The ecological challenge required busines.s to Jbrntulate str(rtegies, in order to a) moke the most effcient use of scarce resources, b) reduce waste ond pollute the enyironment, and c) keep induslrial prctduction v,ithin thc lintit set by nature,s ecological :jy.rtemt. A corporalion culture was directly qnd crit ic(llly Iinkcd to sociol strategy thdt rried to be uchievcd by top nhlnq4(Dlt nt The purpose of lhis reseurch u)os to comparc lhe cerpor(tte cullure in corporate ,social responsibility toward environnrcnt issues belv,een national un.l ntultinalionql corpr.trations in Indonesia. The secontlar.t lturp()s( '*." Io cxtnint thc rclatnnship betneei corporate culture toward cnyironnant issues and its long ^tern econonic pgrfonnance. Research conducted among sutnpla oJ I I2 ncrtional and mulrinotional corporationli in Indonesiq. The results oJthe research itttlicutt'Ll rhat ct) therc w,a.s nostutisticolly signifcant dffirence between nationql arul nulrinurioncrl corporation in htdonc,sru regarcling lheir,\trength of corporate culture tot'r.urd uvironntent issues, b) there wos e positiye relationship hetween slrength of corporatc cullure lo.tuord enr)ironnent iss4es arul long term ece_ nr.tmic performance, bul it wds (r ltt)dc reletionship,r.